The age of uncertainty - Galbraith, John Kenneth 1908-2006 (London British Broadcasting Corporation, 1977)
The distinguished diplomat and economist surveys the ideas and influence of economists and social philosophers, from Adam Snith's day to the present, contrasting the certainties in ninteenth-century economic thought with the uncertainty of today's.
The prophets and promise of classical capitalism -- The manners and morals of high capitalism -- The dissent of Karl Marx -- The colonial idea -- Lenin and the great ungluing -- The rise and fall of money -- The Mandarin revolution -- The fatal competition -- The big corporation -- Land and people -- The metropolis -- Democracy, leadership, commitment.
Based on a BBC television series scheduled for release in 1977.
Includes bibliographical references (pages 345-348) and index.
Keywords: Economics -- History; Economic history